2021
DOI: 10.3390/su13063045
|View full text |Cite
|
Sign up to set email alerts
|

Perceived Green Human Resource Management Practices and Corporate Sustainability: Multigroup Analysis and Major Industries Perspectives

Abstract: The substantial focus on achieving corporate sustainability has necessitated the implementation of green human resource management (GHRM) practices. The purpose of this paper is to reveal the industries’ perspective of the impact of GHRM practices (i.e., green recruitment and selection, green pay and rewards, and green employee involvement and green training) on corporate sustainability practices. Data were collected from 200 human resource professionals in major industrial sectors of a developing country. Par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
77
1
7

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 80 publications
(88 citation statements)
references
References 59 publications
3
77
1
7
Order By: Relevance
“…These findings endorsed the postulation of stakeholder theory that firms are responsible for satisfying the demands of multiple stakeholders within and outside the organization. Our findings are consistent with many previous studies [33,37]. The statistics of OLS and 2SLS shown in Table 4 further reveal that there is a positive impact of the workplace and environmental sustainability on firm financial performance using ROE as a proxy.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…These findings endorsed the postulation of stakeholder theory that firms are responsible for satisfying the demands of multiple stakeholders within and outside the organization. Our findings are consistent with many previous studies [33,37]. The statistics of OLS and 2SLS shown in Table 4 further reveal that there is a positive impact of the workplace and environmental sustainability on firm financial performance using ROE as a proxy.…”
Section: Resultssupporting
confidence: 91%
“…Firms may acquire or enrich their green abilities by the self-efficacy gained through recruitment and selection of new skilled employees or by training already existing employees who could boost their environmental outcomes. They assist firms in promoting cleaner and environmentally friendly production, recycling, and controlling or reducing emissions [37]. Workplace sustainability is considered one of the most important and significant policies of human resource management (HRM) to increase the green spending of resources in organizations and to encourage the cause of a sustainable environment [38].…”
Section: Workplace and Environmental Sustainabilitymentioning
confidence: 99%
“…Some studies have shown that in the past decades, some human resource management methods, such as 360 degree performance evaluation, knowledge management, team building, and motivation-based salary system, have no obvious practical effect in some organizations. One of the important obstacles is the lack of organizational commitment and phased improvement [4][5][6]. In the era of knowledge economy, if enterprises still stick to the mechanical thinking mode and only focus on the local optimization of human resources, it may be difficult to get the expected results.…”
Section: Introductionmentioning
confidence: 99%
“…In Table 4, in the "Professional Development" subcategory, continuous training and development of employees did not seem to be a priority for companies (50.4% of the interviewees completely disagreed that there was such a need). This seems to contradict the current notion that businesses and corporations from all over the world should be peoplecentered and people should therefore be the core of all organizational activities [40,41]. The latter creates long-term value not only for employees, but also consumers, among a realm of different stakeholders [42].…”
Section: Innovative Leadershipmentioning
confidence: 95%